2014
DOI: 10.1002/anie.201407090
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Earth Guests in Polyoxopalladate Chemistry: From Nanocube to Nanostar via an Open‐Shell Structure

Abstract: The three novel, discrete palladium(II)-oxo clusters [CaPd12O8(PhAsO3)8](6-) (CaPd12), [SrPd12O6(OH)3(PhAsO3)6(OAc)3](4-) (SrPd12), and [BaPd15O10(PhAsO3)10](8-) (BaPd15) encapsulating alkaline earth metal ions were prepared and fully characterized by a multitude of solution and solid-state physicochemical techniques. We have discovered a structure-directing template effect induced by the respective size of the alkaline earth guest ion, which determines the detailed condensation arrangement of the peripheral P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 37 publications
0
62
0
Order By: Relevance
“…[9] Recent advances elucidated that the respective size of the guest M allows the detailed condensation arrangement of the peripheral Pd II -oxo shell to be tuned. [10] Nevertheless,asystematic study on the structure-directing effects induced by other noble metal ions besides Pd II has thus far been rather unexplored, although we have demonstrated that it is possible to merge Pd II and Au III into one polyanion. [11] Compared to single-component nanocatalysts,t he catalytic performance of composite nanostructured systems, which are composed of two or more noble metal elements, tends to improve dramatically with higher activity,prolonged lifetime,a nd optimized selectivity,a saunique ensemble of functions from each individual component, hence overcoming the limitation of their single-metal counterparts.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…[9] Recent advances elucidated that the respective size of the guest M allows the detailed condensation arrangement of the peripheral Pd II -oxo shell to be tuned. [10] Nevertheless,asystematic study on the structure-directing effects induced by other noble metal ions besides Pd II has thus far been rather unexplored, although we have demonstrated that it is possible to merge Pd II and Au III into one polyanion. [11] Compared to single-component nanocatalysts,t he catalytic performance of composite nanostructured systems, which are composed of two or more noble metal elements, tends to improve dramatically with higher activity,prolonged lifetime,a nd optimized selectivity,a saunique ensemble of functions from each individual component, hence overcoming the limitation of their single-metal counterparts.…”
mentioning
confidence: 82%
“…[8a,c] However,i ti sd ifficult to directly assign the signals to specific phosphorus atoms owing to the closely spaced resonances ( Figure S4). Therefore,ESI-MS was used to obtain more insight on the stability of both polyanions in both solution and gas phases.T he ESI-MS spectrum of Na-Ag 4 Pd 13 indicates that all major envelopes originate from the Pd 13 core structure ( Figure S5a) 15 shows ad istribution of peaks which can all be unambiguously assigned to ion pairs related to the intact AgPd 15 core (with one Ag I ion present in the center of the polyanion channel), appearing as an ensemble of adducts with different numbers of external Ag I guests ranging from 1t o5( Figure S5b) 10 AgPd 15 ]} 4À ,respectively.These ESI-MS spectra demonstrate that the AgPd 15 core structure is stable in aqueous solution as well as in the gas-phase.A dditional MS assignments are summarized in Table S3.…”
mentioning
confidence: 99%
“…The dopantc ould be an oble metal, [14] metal ions, [15][16][17][18][19] or non-metal ions. [28][29][30][31][32][33][34][35] Polyoxoanions have empty do rbitals in their structures to accept electrons withouts tructure changes. [24][25][26][27] POMs,a saclass of inorganic anionic clusters, have been extensively applied in magnetism, materials science, nonlinear optics, electrical, catalysis, optical, energy,a nd medicineo wing to their redox properties, charged istribution, versatile properties, and rich topology.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] The majority of the reports related to POM-based heterometallic compounds cover examples with Cu as a second metal, [15][16][17] while only a few publications mention the anions' combination with cobalt. [27] Inspired by the reported structure-directing template effect of the metals on the formation of POMs, we decided to study the influence of Ca 2+ and Sr 2+ ions on phosphomolybdate-based structures. [20,21] Another intriguing possibility is the use of alkaline-earth metals as promising templates for discovering new binding motifs with POMs.…”
mentioning
confidence: 99%
“…[23] There are also a number of vanadiumbased polyanions linked by alkaline-earth metals. [27] Inspired by the reported structure-directing template effect of the metals on the formation of POMs, we decided to study the influence of Ca 2+ and Sr 2+ ions on phosphomolybdate-based structures. [27] Inspired by the reported structure-directing template effect of the metals on the formation of POMs, we decided to study the influence of Ca 2+ and Sr 2+ ions on phosphomolybdate-based structures.…”
mentioning
confidence: 99%